Hybrid Prosthesis versus Overdenture: Effect of BioHPP Prosthetic Design Rehabilitating Edentulous Mandible - Hanan Mohsen Al-Asad; Mahmoud Hassan El Afandy; Hebatallah Tarek Mohamed; Magda Hassan Mohamed (International Journal of Dentistry, 2023)
Aim. To compare the BioHPP (biocompatible high-performance polymer) as a substructure for the hybrid prosthesis versus the BioHPP bar supporting and retaining implant overdenture by radiographic evaluation to identify bone height alteration around the implants and to evaluate satisfaction based on visual analoge scale questionnaire. Materials and Methods. Ill-fitting mandibular dentures were chosen for 14 fully edentulous male patients with adequate dental hygiene, enough interarch space, and free of systemic diseases and parafunctional habits. Patients who received new dentures (CDs) were randomly allocated into each group using computer software, and four interforaminal implants were inserted in parallel using a surgical guide. Three months after osseointegration, the patients received either CAD–CAM BioHPP framework hybrid prosthesis (Group I) or BioHPP bar supported and retained overdenture (Group II). Using digital preapical radiography, the bone loss is evaluated 6, 12, and 18 months after insertion. The subjective patient evaluation was done using a questionnaire based on the VAS includes five points for chewing, comfort, esthetics, speech, oral hygiene, and general satisfaction. Results. The overall marginal bone loss (MBL) revealed that Group I (hybrid prosthesis) was more than Group II (bar overdenture) at all intervals in the anterior and posterior implants’ mesial and distal surfaces. The patient satisfaction survey results showed that, after 18 months, the difference was statistically not significant between them all (P>0.05) except for the comfort (for the overdenture group, 4.43 ± 0.53 while the fixed hybrid was 5.00 ± 0.00). Conclusion. BioHPP framework material is an alternative material for implant rehabilitation of edentulous mandible with minimal MBL in BioHPP bar overdenture compared to BioHPP hybrid prosthesis.